POSSIBILITIES OF USING ARTIFICIAL INTELLIGENCE IN THE MODERN FOREIGN LANGUAGE TEACHING SYSTEM (Scientific journal of the Fergana State University, 2025)
Improving the quality of education is one of the priority directions in the process of development of new Uzbekistan. Today, Internet tools based on artificial intelligence are covering all spheres of social life, especially the education system. A lot of empirical research is being conducted in this field, that is, the application of AI (artificial intelligence) in the educational system. Despite this, there are not enough studies on the application of AI in the higher education system of Uzbekistan, especially in the field of foreign language teaching, and its main achievements and shortcomings. In this regard, in this article, the study of the opinions of teachers in the higher education system on the use of ChatGPT in higher education and the main benefits and shortcomings of the process were scientifically analyzed. The scientific research included several stages, in which processes such as selection of participants, interviews and questionnaires, coding of answers before analysis, and analysis of results were carried out. According to the results of the research, the opinions of professors and teachers on the use of AI in foreign language teaching are mostly positive, and they also listed some shortcomings. The results of this study provide important results for teachers in the foreign language teaching system, syllabus designers, and researchers conducting scientific research in the field.